Plasminogen Has a Broad Extrahepatic Distribution - Zhang, Lu; Seiffert, Dietmar; Fowler, Bruce J.; Jenkins, George R.; Thinnes, Therese C.; Loskutoff, David J.; Parmer, Robert J.; Miles, Lindsey A. (Thrombosis and Haemostasis, 2002)
Plasmin is the major enzyme that dissolves fibrin in the vasculature and the predominant source of its zymogen, plasminogen, is liver. However, plasmin has a broad substrate spectrum and, if present in other tissues, may perform additional functions. We tested the hypothesis that plasminogen is expressed broadly extrahepatically. A sensitive and specific isotopic quantitative RT-PCR assay was developed to detect plasminogen mRNA from total RNA isolated from C57BL/6J mice tissues. Plasminogen mRNA was detected in adrenal, kidney, brain, testis, heart, lung, uterus, spleen, thymus and gut. Of these tissues, adrenal had the highest plasminogen mRNA content. In situ hybridization was utilized to localize plasminogen mRNA expressing cell types. Besides hepatocytes, positive cells were identified in both adrenal and kidney medullae and cortexes. Plasminogen mRNA expression was detected in cerebral, hippocampal and cerebellar neurons. Plasminogen mRNA was detected in cells in early stages of spermatogenesis in testis, present in the cortex and medulla of the thymus and in splenic white and red pulps. Our results suggest that the plasminogen gene is expressed broadly in extrahepatic tissues. Thus, tissues separated by local anatomic barriers as well as tissues accessible to circulating plasminogen have the capacity to provide local sources of plasminogen.
Keywords: Plasminogen; adrenal; brain; testis; thymus